(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
In this article, we focus on the scaling theory of Abraham et al. without and with a magnetic field on the metallic side of the Metal-Insulator Transition (MIT) for the three-dimensional system \(^70\)Ge: Ga, at very low temperatures. In particular, we have determined the zero temperature conductivity critical exponent when the MIT transition occurs with the variation of the impurity concentration \((υ=0.503)\) and with the application of a magnetic field \((υ=1.06)\). We have also estimated the critical magnetic field \(B_C\) that separates the metallic behavior \((B<B_C)\) from the variable-range hopping regime \((B>B_C)\). The data are for a \(^70\)Ge: Ga sample prepared and reported by Itoh et al., Physical Review Letters 77 (1996), 4058 and Watanabe et al., Physical Review B 60 (1999), 15817.